ChemInform Abstract: Lewis Base Activation of Silyl Acetals: Iridium‐Catalyzed Reductive Horner—Wadsworth—Emmons Olefination. Issue 16 (March 2016) - Dakarapu, Udaya Sree; Bokka, Apparao; Asgari, Parham; Trog, Gabriela; Hua, Yuanda; Nguyen, Hiep H.; Rahman, Nawal; Jeon, Junha
Abstract: A convenient scalable transformation of multiple challenging aryl, hetaryl, alkyl, and alkinyl esters as well as diesters into silyl acetals and the in‐situ transformation of the latter into enoates is elaborated.